2021
DOI: 10.1055/a-1423-8961
|View full text |Cite
|
Sign up to set email alerts
|

Recent Antiviral Treatment and Vaccination Strategies Against SARS-CoV-2

Abstract: Since the end of 2019, the novel severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) has been spreading worldwide and has caused severe health and economic issues on a global scale. By the end of February 2021, more than 100 million SARS-CoV-2 cases had been reported worldwide. SARS-CoV-2 causes the coronavirus disease 2019 (COVID-19) that can be divided into three phases: An early phase with fever and cough (phase I), a pulmonary vascular disease (phase II) and a hyperinflammatory syndrome (phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…Der Eintritt des umhüllten, einzelsträngigen RNA-Virus SARS-Cov-2 hängt hauptsächlich ab von der Bindung des Spike-Proteins (S-Protein) an spezifische Transmembranrezeptoren, wie das Angiotensin-konvertierende-Enzym 2 (ACE-2), und an transmembrane Serinproteasen, wie TMPRSS2 5 , 6 , 7 . Beide Bindungsstellen werden auf Netzhautzellen exprimiert und machen damit eine Beteiligung des retinalen Gefäßsystems und der Netzhautschichten durch eine viral induzierte endotheliale Dysfunktion möglich 8 , 9 , 10 .…”
Section: Introductionunclassified
“…Der Eintritt des umhüllten, einzelsträngigen RNA-Virus SARS-Cov-2 hängt hauptsächlich ab von der Bindung des Spike-Proteins (S-Protein) an spezifische Transmembranrezeptoren, wie das Angiotensin-konvertierende-Enzym 2 (ACE-2), und an transmembrane Serinproteasen, wie TMPRSS2 5 , 6 , 7 . Beide Bindungsstellen werden auf Netzhautzellen exprimiert und machen damit eine Beteiligung des retinalen Gefäßsystems und der Netzhautschichten durch eine viral induzierte endotheliale Dysfunktion möglich 8 , 9 , 10 .…”
Section: Introductionunclassified
“…Immunotherapy of potentially lethal infections, lacking specific preventive and therapeutic options, with passive immunization with convalescent plasma was successfully used in other viral diseases such as SARS, Ebola or influenza A (H5N1) [ 6 , 7 , 8 , 9 ]. The experimental treatment of SARS-CoV-2 infection with convalescent plasma has therefore been proposed particularly in the vulnerable cohort of high-risk patients [ 10 , 11 , 12 , 13 , 14 , 15 ]. Initial studies reported an improvement in the clinical condition and survival in patients undergoing plasma treatment [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the progress of the pandemic, major advances have been achieved in understanding, prevention, and treatment of the disease. COVID-19 can be subdivided in three different phases: An early phase with viremia, fever and cough (phase I), a pulmonary vascular disease (phase II) and a hyperinflammatory syndrome (phase III) [ 13 ]. Notably, the viral replication plays an important role in the early stage of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current lack of specific drugs, vaccination is an effective way to control the COVID-19 pandemic (8). However, sporadic adverse events in the cardiovascular system (9,10) were reported to occur after SARS-CoV-2 vaccination, such as immune thrombotic thrombocytopenia (11), idiopathic thrombocytopenic purpura, arterial thromboembolic events (such as ischemic stroke), hemorrhagic events (such as hemorrhagic stroke), and cerebral venous sinus thrombosis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%